ANALISA PERFORMASI VOICE ISSUE BAD QUALITY DI LOKASI TAMAN WISATA ALAM PUNTI KAYU PALEMBANG - SAYUTI, AKHMAD (Perkumpulan Cendekia Muda Kreatif Indonesia, 2023)
The WCDMA network is the third generation of telecommunications history. The aim is to strengthen coverage but in reality it becomes a source of new problems for the progress of telecommunications networks by not measuring and ignoring old BTS. In this case, the Punti Kayu Nature Tourism Park location is the checking location that is experiencing problems. Checking using the drive test/walktest method is the beginning of identifying a problem that occurs. Next, optimization and implementation will be carried out so that the Telkomsel network will always be good. The BTS that covered the Punti Kayu Nature Tourism Park location in the initial stage was the LtMurod BTS, 1.2KM away, but the distance was far from the range of the BTS so that the signal received at that location was very bad, whether it was voice or idle in the building. However, after optimization by resetting the transmit power of the closest BTS, namely LdMurod and Moatik2, the result was that the Moatik2 BTS with a distance of 100 meters was much more dominant in covering that area. Taking into account the distance of the BTS to the problematic location. Judging from the results of this research, outdoor areas do not experience problems. The problematic location is in the indoor area, in the rooms in the office section of the Punti Kayu Nature Tourism Park location. Checking the initial stage of indoor(voice) for the RSCP value, no one was in the very good category, 18.99% was in the good category, 80.35% was in the fair category and 0.66% was in the bad category, while the final stage of indoor(voice) for the RSCP value was 100% in the very good category. In the initial stage of indoor (voice) checking, the EC/NO value was 2.32% in the very good category, 49.08% in the good category, 47.13% in the fair category and 1.47% in the bad category. Meanwhile, the final stage indoor (voice) for the EC/NO value of 94.64% is in the very good category.